The Role of Schema Theory in The Interpretation of Language Advertising - Djellil, Khadra (My University, 2017)
The diffusion of advertising as a social phenomenon underscores the need to understand how the client will interpret and understand the language of this discourse based on their schematic knowledge. Thus, the advertising language is different from the usual language. Because, he tries to transmit a private message to the mass public in a particular society. This thesis aims to study the role of schema theory in the interpretation of Algerian discursive advertising. The choice of the sample in this study is selected from different types of media; Visual, audio and written to analyze the use of language between the advertiser and the client. The study shows that despite the fact that the use of schematic theory can give the interpreter a variable meaning. But the message that goes beyond the advertising message is the same. It refers to the context and the cultural context.
The Algerian Context
Keywords: Speech language; Advertising language; Algeria